PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK PADA KANTOR DINAS KEPENDUDUKAN KOTA BATAM - Suhardi, Suhardi (LLDIKTI Wilayah X, 2018)
The purpose of this study is to describe how the public perception of service at Kantor Dinas Kependudukan of Batam City in issuing the letter moved, KTP/KK, birth certificate, and other public services so that can be used as a reference for the relevant offices in improving the quality of service for the implementation of good governance. The method used in this research is descriptive qualitative and naturalistic. Sources of data are taken from informants with backgrounds as the perpetrators of the event: staff / service officers and staffs and service users directly involved at the time. The results showed that the tangible dimension, which is in accordance with the expectations of service user perceptions is the indicator appearance of employees, and using tools in the service process, while indicators that are not in accordance with the perception of service users is convenience place, still not comfortable; infrastructure; employee discipline; provide convenience in serving; access to services, assessed still not running in accordance with the expectations of service users. Judging from the dimensions of reliability, dimensions responsiveness, and dimensions assurance in general has been running as expected perceptions of service users, only in the implementation is still felt slow. The Empathy dimension, which has been going according to the user's perception of service is that the employee prioritizes the interests of the service user; providing service with courtesy; do not discriminate, serve and appreciate every service user, but in empathy dimension is still there that not yet according to expectation of service user perception is indicator employee service yet serve with attitude of friendliness.Tujuan penelitian ini adalah untuk mendeskripsikan bagaimana persepsi masyarakat terhadap pelayanan pada Dinas Kependudukan Kota Batam dalam mengeluarkan surat pindah, KTP/KK, Akte Kelahiran, dan pelayanan publik lainnya sehingga dapat dijadikan acuan bagi dinas terkait dalam meningkatkan kualitas pelayanan demi terlaksananya good governance. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dan naturalistic. Sumber data diambil dari informan yang berlatar belakang sebagai pelaku peristiwa yaitu: Staf/petugas layanan dan jajaranya serta pengguna layanan yang terlibat secara langsung pada saat itu. Hasil penelitian menunjukan bahwa dimensi tangible, yang sudah sesuai dengan harapan persepsi pengguna layanan adalah indikator penampilan pegawai, dan menggunakan alat bantu dalam proses layanan, sedang indikator yang belum sesuai dengan persepsi pengguna layanan adalah kenyamanan tempat, masih belum nyaman; sarana/prasarana; kedisplinan pegawai; memberi kemudahan dalam melayani; akses pelayanan, dinilai masih belum berjalan sesuai dengan harapan pengguna layanan. Dilihat dari dimensi reliability, dimensi responsiveness, dan dimensi assurance secara umum sudah berjalan sesuai harapan persepsi pengguna layanan, hanya dalam pelaksanaannya masih dirasakan lambat. Dimensi empathy, yang sudah berjalan sesuai haparan persepsi pengguna layanan adalah pegawai mendahulukan kepentingan pengguna layanan; memberikan layanan dengan sikap sopan santun; tidak melakukan diskriminatif, melayani dan menghargai setiap pengguna layanan, namun pada dimensi empathy ini masih ada yang belum sesuai harapan persepsi pengguna layanan adalah indikator pegawai pelayanan belum melayani dengan sikap keramahan.